ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI SENAM AEROBIK LOW IMPACT TERHADAP PENURUNAN BERAT BADAN PADA REMAJA DI KELUARGA TN.F DI RT 01 RW 03 DESA RANCAGONG KECAMATAN LEGOK KABUPATEN TANGERANG - Siti Luthfia Awanda (2022)
Obesity is a condition when the Body Mass Index (BMI) is above 30 kg/m2 which is one of the problems that occurs in many children and adolescents in the world. Obesity can cause serious health problems in adolescents. Adolescents who are obese, the risk for problems with the heart and blood flow will increase as the teenager grows up. Therefore, the problem of obesity in adolescents must be addressed immediately. One therapy that can be done is low impact aerobic exercise. The purpose of this study was to determine the effect of low impact aerobic exercise on weight loss of obese adolescents. The number of respondents involved were two people where both were given the same intervention. The level of effectiveness was measured using body weight before and after the intervention. The results of this study found that there was a significant weight loss in both respondents. So it can be concluded that low impact aerobic exercise has an effect on weight loss. The author recommends low impact aerobic exercise as a complementary therapy that can be done.